KATA-KATA PINJAMAN BAHASA INGGRIS DALAM BAHASA INDONESIA PADA KORAN HARIAN â€œMANADO POSTâ€ - Sengkey, Syutrika Dian (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled â€œKata-Kata Pinjaman Bahasa Inggris dalam Bahasa Indonesia pada Koran Harian Manado Postâ€. The objectives of this research are to find out the kinds and the changes of the meanings of English loan words in Indonesian language. In analyzing the data, the writer uses Haugenâ€™s theory to find out the types and Baughâ€™s theory to get the changes of the meanings. To support the analysis, the writer uses Oxford Dictionary and Kamus Besar Bahasa Indonesia. The results of this research show that based on the theory of Haugen there are three kinds of loan word. Those are loan word without phonemic substitution, loan word with partial phonemic substitution, loan word with complete phonemic substitution and there are two kinds of the changes of meaning such as extention and narrowing, but regeneration and degeneration process are not found in those loan words. Keywords: Loan Words, Change of Meaning, Socioliguistic, Manado Post Newspaper